O monstro de olhos verdes em Dom Casmurro e Órfãos do Eldorado - Martins, Paulo Maria (2022)
This dissertation intends to understand the jealous, like a symbolic building of expression of power, can be read in Dom Casmurro (1899), by of Machado de Assis, and Órfãos do Eldorado (2008), by of Milton Hatoum. We want do discuss that jealous goes beyond the doing and is considered like a symbolic violence, with a feeling of domination of a class on other. In Dom Casmurro (1899) the jealous of Bentinho destroys his marriage and make him a “casmurro”, insensible at the sufferings of his wife, and the son, that he believes that he is not the father. In a patriarchal society, the narrator shows the symbolic violence when silence the woman that is accused of adultery. In Órfãos do Eldorado (2008), there is a dispute between father and son for the permanence of the social situation. Amando, a powerful man of the Amazonas, is owner of the shared capital – social relationships that can be changed in resources of domination (BOURDIEU, 2003) –, so, expects the child perpetuate his domain. The father, egocentric, recuses to see his child to envolve itself with people that looks less, the dominated – poors, the Riversides, employees, and indians. The jealous, the zeal, the anger, that father feels for the son, is for Arminto more free and less committed with the power and status, although enjoy of this conditions. In the doing, from the sociocultural point of view, the jealous is not showed like a romanticized feeling, but mainly like a mechanism used to express and show the symbolic violence. The search is done with a analyse about the two doings, because we believe than make us understand, of a right way, the relation between the express classes by the Family relationships, but, by the metaphorical way, we can still see the reflection about Brazil in the final of the 19th century and in the beginning of the 20th century. Both narratives speak of memory reports, contributing for we observe the mixed feelings and the unveiling of the social life for the choices of what do want remember by the sotytellers. Besides that, is a productive analyse about the space in the two narratives, because this class of narrative ends incorporating materials and symbolics characteristics of fight of classes.